Analisis dampak tingkat literasi keuangan syariah, religiusitas dan akses layanan terhadap penggunaan produk keuangan Syariah - Ahmad Fauzul Hakim Hasibuan; Munardi; Ichsan (IAIN Langsa, 2020)
This study used a quantitative approach involving 32 respondents from Gampong Pusong fishermen. The sampling technique was carried out using stratifi ed random sampling. This study is based on primary data in the form of a questionnaire collected from all respondents which aims to see the impact of Islamic financial literacy on religiosity and service accents on the use of Islamic fi nancial products. This is due to the privilege of Aceh province as a locomotive for sharia fi nance with the issuance of qonun no 11 of 2018 concerning Islamic finance. Methods of data analysis using Multiple Linear Regression analysis with F-test and T-test. Whereas for testing the instrument using the validity test, reliability test, and classical assumption test. The results of the study can be concluded that the regression model has been made to determine the area of rejection of the hypothesis. The rejection area is if F-count > F-table, namely 18.041> 2.71, then the decision H0 is rejected. Or it can be seen from the signifi cance value, namely if the p-value <α, (0.000 <0.05), then H0 is rejected. So that Islamic Financial Literacy (X1), Religiosity (X2), and Access Aff ordability (X3) together affect Product Use (Y) or the model that has been made is correct.